Evaluating the drop of electrochemical performance of Ni/YSZ and Ni/ScSZ solid oxide fuel cells operated with dry biogas. (8th December 2020) - Arifin, Nor Anisa; Shamsuddin, Abd Halim; Steinberger‐Wilckens, Robert
Summary: This work is aimed at evaluating the influence of carbon deposition on the power density drop of in‐house fabricated Ni/YSZ and Ni/ScSZ solid oxide fuel cells (SOFCs) operating in dry internal reforming of simulated biogas (CH4 /CO2 = 2). An immediate drop of open‐circuit voltage (OCV) and maximum power densities is observed when the fuel changes from hydrogen to biogas, 86.5% and 33.3% for the Ni/YSZ and Ni/ScSZ cells, respectively with mass transfer polarisation dominates Ni/YSZ polarisation. Carbon deposition is investigated as the cause of the reduction in performance by quantification of deposited carbon by temperature programmed oxidation (TPO) and catalytic activity test. Results from TPO analysis show unexpectedly higher amount of carbon on the Ni/ScSZ cells (2.35 × 10 −3 mgC/mgcat ) as compared to Ni/YSZ (5.68 × 10 −4 mgC/mgcat ) despite higher performance of the former. Catalytic activity tests reveal a low carbon oxidation rate compared to an initially higher methane decomposition reaction, leading to carbon deposition in both cells, in which the methane decomposition reaction of Ni/ScSZ is higher. Different effects are observed on the pellets, where the carbon deposited on Ni/YSZ deactivates the reforming reaction sites as quick as 20 minutes into the operation, whereas carbon deposited on the Ni/ScSZ pellet did not show the same blocking effect on the catalyst due to the different carbon morphology formed. A graphitic whisker‐like rod structure is observed on Ni/ScSZ while amorphous non‐crystalline carbon covers the Ni/YSZ pellets with 3 hours exposure to high methane content dry biogas (CH4 /CO2 = 2). The difference of carbon structure affects the amount of carbon quantified in the TPO analysis where most of the amorphous carbon oxidises while some of the graphitic carbon deposits remain. Abstract : Three times higher amount of carbon found on Ni/ScSZ despite significantly better performance as compared to Ni/YSZ. Catalytic activity tests reveal a low carbon oxidation rate compared to an initially higher methane decomposition reaction, leading to carbon deposition. Methane decomposition reaction of Ni/ScSZ was higher which release more hydrogen, inevitably accompanied by more carbon deposited. Different carbon formed on the cells where graphitic carbon formed on Ni/ScSZ while amorphous carbon formed on Ni/YSZ.